Protection of Personal Data in Electronic Medical Records (RME) in Healthcare Facilities Reviewed from a Human Rights Perspective - Seputra, Hawreyvian Rianda; Kuntardjo, Carolina; Riyandini, Krisnandifa Marshafira; Purwanto, Nanang Zuli (Rechtsvinding, 2025)
The advancement of digital technology has transformed medical record systems from conventional formats to Electronic Medical Records (EMRs). While EMRs enhance healthcare service efficiency, they also introduce challenges concerning the protection of patients’ personal data. Privacy issues have become increasingly critical and require examination from a human rights perspective, particularly the right to privacy and personal data protection. This study employs a normative qualitative method focusing on legal frameworks, human rights principles, and relevant regulations. Data were collected through literature reviews of national laws, international human rights conventions, academic journals, and official documents. A descriptive-qualitative analysis was used to construct a systematic and logical scientific argument. Findings show that patient data protection in EMRs is regulated under the Personal Data Protection Law and Ministry of Health regulations, emphasizing confidentiality, data integrity, and security in accordance with human rights standards. However, practical implementation faces several challenges, including inadequate technological infrastructure, low awareness among healthcare personnel, and weak oversight and law enforcement. These gaps result in a high risk of data breaches, driven by technical vulnerabilities, human error, misuse of access by internal staff, and the absence of effective monitoring systems. Although patients' rights to access and correct their data are legally acknowledged, consistent implementation across healthcare facilities remains limited.